From Community Capital to Sustainable Rural Livelihood: Exploring Green Development Program in Masoso, Indonesia - Syafar, Muhammad; Ulumi, Helmy Faizi Bahrul (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2021)
Community capital has approached to formulate a sustainable rural livelihood. As an agreement in the world development challenges, it have been designed in the framework of Sustainable Development Goals (SDGs) that was supported by the United Nations as a global effort to attain 169 targets, such as natural resources management for sustainable rural development. This article aims to analyze community empowerment on green development to strengthen energy self-sufficient villages based on the community capital. The method in this research used the qualitative approach that was used in order to obtain a comprehensive understanding of all phenomena that occurred in the study of Masoso village, Indonesia. The result of the discussion found that the implementation of green development through micro-hydro power plants supported by the village fund, and has contributed for local community prosperity. This study concludes that the adherence of the community to traditional institutions and local wisdom needed to preserve as the basis of community collectivity to conserve natural resources. New opportunities of local economic activities on integrated agriculture could promote socio-economic development in the modern era through strengthening of farmer groups and community development.